2013
DOI: 10.1002/jls.21277
|View full text |Cite
|
Sign up to set email alerts
|

The Common Language of Leadership

Abstract: As our complex society continues to call for leadership across all career fields, preparing leaders at the college level can be challenging. This article outlines the results of a comprehensive examination of learning outcomes of 475 academic programs within 72 academic accrediting organizations in regard to student leadership development. The purpose of the current study was twofold: (a) to understand better what competencies college students need to develop in order to engage in leadership in their respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 11 publications
0
47
0
Order By: Relevance
“…The social sciences and humanities have explored the theoretical nature of leadership, and applications of natural sciences have been used to study leadership, all informing the foundational knowledge of leadership and its programs (Harvey & Riggio, ). Applied disciplines, such as business, education, agriculture, and engineering, have developed specialisms and interest in the practice and application of theoretical leadership knowledge (Seemiller & Murray, ). From a knowledge, or academic, perspective, leadership is multidisciplinary and this is reflected in the diversity of programs and their locations that have emerged across institutions of higher education.…”
Section: Interdisciplinarity Of Leadershipmentioning
confidence: 99%
“…The social sciences and humanities have explored the theoretical nature of leadership, and applications of natural sciences have been used to study leadership, all informing the foundational knowledge of leadership and its programs (Harvey & Riggio, ). Applied disciplines, such as business, education, agriculture, and engineering, have developed specialisms and interest in the practice and application of theoretical leadership knowledge (Seemiller & Murray, ). From a knowledge, or academic, perspective, leadership is multidisciplinary and this is reflected in the diversity of programs and their locations that have emerged across institutions of higher education.…”
Section: Interdisciplinarity Of Leadershipmentioning
confidence: 99%
“…Given the great degree of variance in formal leadership programs (Brungardt, Greenleaf, Brungardt, & Arensdorf, ; Jenkins & Owen, ; Seemiller & Murray, ), a fundamental question arises for all leadership educators, scholars, and practitioners: What does it mean for our discipline or field of study if we do not all agree about the basic nature of the field? Given the great variety of different leadership programs that are all teaching under a similar name, but in many cases are teaching toward very different outcomes, how do we most effectively capture the diversity of the field while addressing issues of validity, credibility, and disciplinary development?…”
mentioning
confidence: 99%
“…A review of literature revealed a long history of many approaches to categorization of leadership competencies. 10,15,16,23,25,28,29,32 After review of the prior research and the results of the in-depth interviews in phase one, Seemiller's taxonomy 28,29 was selected as the best fit to discuss.…”
Section: Question Developmentmentioning
confidence: 99%
“…28,29 During the question writing phase, it was realized that responses relating to Seemiller's "values" would not be useful due to limitations presented by these types of questions. It was noted that industry personnel might be presented with challenges when asked to respond about the beliefs of others.…”
Section: Question Developmentmentioning
confidence: 99%
See 1 more Smart Citation